Perancangan Promosi Grand Rocky hotel Dalam bentuk Media Audio Visual - MHD. ILHAM TAHER, Drs. Syafwan, M.Si., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Along with the progress of the development of information media and systems in the Digital era and also soaring tourists in the area around the city of Bukittinggi so many hotels and inns compete to attract tourists who need accommodation and can enjoy the natural beauty, history, cuisine and culture. Grand Rocky Hotel has facilities with a four-star standard for a hotel in the Bukittinggi area on some sides there is still a shortage, Rocky Hotel is also equipped with tourist safety facilities It is suitable for tourists who want to enjoy the tourist objects around Bukittinggi. The target is not only domestic tourists but foreign tourists. In the past year, the number of tourists visiting the city of Bukittinggi reaches approximately 500-600 thousand tourists, including 75% of domestic tourists, and 25% of foreign tourists, Grand Rocky Hotel Rooms must be ready to compete to get tourists who need Hotels.Using analysis and interviews with media promotion media campaign managers who are interesting to support the promotional content of Grand Rocky Hotel in getting target consumers. The author chose promotion in the form of Audio Visual media, where promotion using Audio Visual was able to bring information and excellence of Grand Rocky hotels to be accessible on the internet and social media. In addition to promotion in the form of Audio Visual media as well as several other promotional media, to support the main media promotion of Grand Rocky hotels, such as posters, flyers, Xbanner, paperbag t shirts, mugs, pins, cd covers, and cd labels.Keywords: Media promotion set, Grand Rocky Hotel video.